The Effect of Audiovisual Education about HIV/AIDS on HIV/AIDS Knowledge in Senior High School 1 Rasau Jaya Students - AFIFAH FAUZIAH; Rahmawati, Nadia; Fradianto, Ikbal (Jurnal Ilmiah Kesehatan, 2025)
Adolescents are vulnerable to various health risks, including HIV/AIDS. Kubu Raya Regency had a significant increase in HIV/AIDS cases, highlighting the need for health education. This study analyzes the effect of audiovisual education about HIV-AIDS on the HIV/AIDS knowledge in Senior High School 1 Rasau Jaya students. It was a pre-experiment with a one-group pre-test and a post-test design without using a control group. The population was 488 students of the 11th and 12th grades of Senior High School 1 Rasau Jaya, with a sample size of 60 students. Data collection was conducted offline by providing audiovisual education about HIV/AIDS and distributing questionnaires. The instrument for knowledge of HIV/AIDS used the 18-item HIV Knowledge Questionnaire (HIV-KQ-18). Data analysis used the Wilcoxon test. The respondents were 15-19 years old, male (63.3%), and 12th grade (51.7%). They had been exposed to information about HIV/AIDS (86.7%), the most common source of information being the internet (60.7%). The median pre-test knowledge score was 50.00, increasing to 77.70 in the post-test. The Wilcoxon test resulted in p=0.000 (p<0.05), indicating a difference in HIV/AIDS knowledge before and after audiovisual education about HIV/AIDS in students. Therefore, there was a significant effect of audiovisual education about HIV/AIDS on HIV/AIDS knowledge in students. In conclusion, Audiovisual education about HIV/AIDS affects HIV/AIDS knowledge in Senior High School 1 Rasau Jaya students. These findings underscore the importance of innovative educational approaches, like audiovisual media, in enhancing adolescents' understanding of HIV/AIDS.